2008
DOI: 10.1055/s-2008-1039786
|View full text |Cite
|
Sign up to set email alerts
|

Das Synovia-Volumen gesunder und arthrotischer menschlicher Kniegelenke*

Abstract: The volume of synovial fluid in human knee joints was determined by the dilution method through the intra-articular injection of 35 ml 0.5% hydroxyethyl starch in saline. In 15 control knees the mean synovial volume was 6.7 +/- 2.3 ml (mean +/- SD). In patients with latent gonarthrosis we found a mean intra-articular volume of 13.6 +/- 7.4 ml (n = 21) and in activated gonarthrosis 24.2 +/- 16.3 ml (n = 34). All 3 groups differ significantly. After entire aspiration of the effusion, we found yet 13.4 +/- 4.4 ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In particular, the in vitro results showed that CG negatively affects chondrocyte viability and proliferation at 1.5 mg/mL, a concentration that, given the therapeutic protocol proposed for CG (two performed at 15 days apart and the third at one month after the last injection) and the volume of the synovial fluid in the symptomatic OA knee joint (>10 mL) [33,34], can never be reached in the clinical setting. These results are in contrast with previous observations by Furuzawa et al [17] who exposed cartilage tissue from five patients with OA for 7 days to 1% (0.6 µg/mL, MW unknown) porcine polymerized-collagen and observed a 3- to 6-fold increase in cell proliferation, but are consistent with those by Nakatani et al [35] who exposed ATDC5 cells, a murine chondrocyte cell line, to porcine hydrolyzed collagen (1 mg/mL) with an average molecular weight of 5 kDa and did not observe any effect on proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the in vitro results showed that CG negatively affects chondrocyte viability and proliferation at 1.5 mg/mL, a concentration that, given the therapeutic protocol proposed for CG (two performed at 15 days apart and the third at one month after the last injection) and the volume of the synovial fluid in the symptomatic OA knee joint (>10 mL) [33,34], can never be reached in the clinical setting. These results are in contrast with previous observations by Furuzawa et al [17] who exposed cartilage tissue from five patients with OA for 7 days to 1% (0.6 µg/mL, MW unknown) porcine polymerized-collagen and observed a 3- to 6-fold increase in cell proliferation, but are consistent with those by Nakatani et al [35] who exposed ATDC5 cells, a murine chondrocyte cell line, to porcine hydrolyzed collagen (1 mg/mL) with an average molecular weight of 5 kDa and did not observe any effect on proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Explants ( n = 7 per group) were cultured for 24 hours prior to assignment to one of the following treatment groups: 0.25% bupivacaine, 0.125% bupivacaine, 0.0625% bupivacaine, 1% lidocaine, 0.5% lidocaine, betamethasone acetate, methylprednisolone acetate, and triamcinolone. The concentration for each treatment group was based on the average volume of synovial fluid found in a human knee joint (7 mL) 13 and the volume of drug required to obtain the desired concentration ( Table 1 ). Explants were cultured in 1 mL of treatment or control media and incubated at 37°C with 5% CO 2 at 95% humidity for either 24 hours or 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…Accumulation of large numbers of cartilage particles on the synovial intima could be further driven by increased synovial fluid effusion and turnover during OA. Even considering the reported concentrations of 100–500 particles/ml, with estimations of total volume and turnover rates for synovial fluid, millions of particles could accumulate on the synovium over the course of years of continuous cartilage degradation as OA progresses. It will be important for future work to understand the long‐term fate of wear particles in the joint, with respect to rates of generation and attachment to the synovial intima versus clearing via phagocytosis and enzymatic breakdown.…”
Section: Discussionmentioning
confidence: 99%